The tradition of Hermes Trismegistus : the Egyptian priestly figure as a teacher of Hellenized wisdom - Bull, Christian H. (Religions in the Graeco-Roman World, 2018)
In The Tradition of Hermes Trismegistus , Christian H. Bull argues that the treatises attributed to Hermes Trismegistus reflect the spiritual exercises and ritual practices of loosely organized brotherhoods in Egypt. These small groups were directed by Egyptian priests educated in the traditional lore of the temples, but also conversant with Greek philosophy. Such priests, who were increasingly dispossessed with the gradual demise of the Egyptian temples, could find eager adherents among a Greek-speaking audience seeking for the wisdom of the Egyptian Hermes, who was widely considered to be an important source for the philosophies of Pythagoras and Plato. The volume contains a comprehensive analysis of the myths of Hermes Trismegistus, a reevaluation of the Way of Hermes, and a contextualization of this ritual tradition.